Declinatoir Exception Rejection Analysis on The Application of The Principles of Simple Fast and Low Costs in Murabahah Financing in The Bukittinggi Religious Courts - Afkar, Afkar; Elimartati, Elimartati; Arianti, Farida; Rahmi, Zikra (IAIN Batusangkar, 2024)
This research examines the application of the principles of fast, simple, and low-cost proceedings in murabahah financing disputes at the Bukittinggi Religious Courts. Specifically, it addresses the issue of declinatory exceptions filed by defendants, which impact the efficiency of the judicial process. These principles are critical for ensuring effective and equitable access to justice. The study aims to analyze the impact of rejecting declinatory exceptions on the trial process in murabahah financing cases. It also evaluates how the principles of fast, simple, and low-cost judicial proceedings are implemented in such disputes. A qualitative research method with a case study approach was employed. Data collection involved analyzing case records, judicial decisions, and related legal principles to understand the implications of declinatory exceptions on court efficiency. The findings indicate that the rejection of the declinatory exception by the panel of judges led to delays in the trial process without valid legal justification. The interim decision, which affirmed the Bukittinggi Religious Court's authority, contradicted the principle of expedited proceedings, thus increasing trial duration and costs. The study concludes that rejecting declinatory exceptions without proper justification undermines the principles of fast, simple, and low-cost trials. Judicial practices should align with these principles to improve efficiency in murabahah financing dispute resolution.